Remote electrical neuromodulation for migraine prevention: A double‐blind, randomized, placebo‐controlled clinical trial. Issue 3 (27th January 2023) - Tepper, Stewart J.; Rabany, Liron; Cowan, Robert P.; Smith, Timothy R.; Grosberg, Brian M.; Torphy, Bradley D.; Harris, Dagan; Vizel, Maya; Ironi, Alon; Stark‐Inbar, Alit; Blumenfeld, Andrew M.
Abstract: Objective: To assess the clinical efficacy of remote electrical neuromodulation (REN), used every other day, for the prevention of migraine. Background: Preventive treatment is key to managing migraine, but it is often underutilized. REN, a non‐pharmacological acute treatment for migraine, was evaluated as a method of migraine prevention in patients with episodic and chronic migraine. Methods: We conducted a prospective, randomized, double‐blind, placebo‐controlled, multi‐center trial, with 1:1 ratio. The study consisted of a 4‐week baseline observation phase, and an 8‐week double‐blind intervention phase in which participants used either REN or a placebo stimulation every other day. Throughout the study, participants reported their symptoms daily, via an electronic diary. Results: Two hundred forty‐eight participants were randomized (128 active, 120 placebo), of which 179 qualified for the modified intention‐to‐treat (mITT) analysis (95 active; 84 placebo). REN was superior to placebo in the primary endpoint, change in mean number of migraine days per month from baseline, with mean reduction of 4.0 ± SD of 4.0 days (1.3 ± 4.0 in placebo, therapeutic gain = 2.7 [confidence interval −3.9 to −1.5], p < 0.001). The significance was maintained when analyzing the episodic (−3.2 ± 3.4 vs. −1.0 ± 3.6, p = 0.003) and chronic (−4.7 ± 4.4 vs. −1.6 ± 4.4, p = 0.001) migraine subgroups separately. REN was also superior to placebo in reduction of moderate/severe headache days (3.8 ± 3.9 vs. 2.2 ± 3.6, p = 0.005), reduction of headache days of all severities (4.5 ± 4.1 vs. 1.8 ± 4.6, p < 0.001), percentage of patients achieving 50% reduction in moderate/severe headache days (51.6% [49/95] vs. 35.7% [30/84], p = 0.033), and reduction in days of acute medication intake (3.5 ± 4.1 vs. 1.4 ± 4.3, p = 0.001). Similar results were obtained in the ITT analysis. No serious device‐related adverse events were reported in any group. Conclusion: Applied every other day, REN is effective and safe for the prevention of migraine.